Analisis Desain Boardgames Edukasi Satwa Endemik dan Belajar Bahasa Arab - Dzikrul Akbar; Choirul Anam (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
As a country with the largest megabiodiversity in the world, which has many endemic animals. Indonesia is also included as a country with a high rate of biodiversity extinction. Of course, this should receive more attention and become our collective responsibility. One of them is by introducing endemic animals by playing while learning through teaching props at school in the form of board games. This is considered effective because in schools where children use their time to study, it makes it easier to distribute education. And don't forget the delivery of education is also accompanied by learning in the school, one of which is Arabic. With all aspects of this relationship, it is hoped that boardgames as an educational medium can be successful The method used in this research is the mix method by distributing questionnaires to 30 respondents and conducting field case studies. The analysis used is using design analysis and needs analysis based on literature studies, data obtained in case studies and questionnaire results. The results of this study resulted in a boardgames design with the type of educational game with a party game theme with a cartoon design style.